2011
DOI: 10.1016/j.jallcom.2011.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SnO2 doping on microstructural and electrical properties of ZnO–Pr6O11 based varistor ceramics

Abstract: a b s t r a c tZnO-Pr 6 O 11 based varistor ceramics doped with 0-2.0 mol% SnO 2 were fabricated by sintering samples at 1300 • C for 2 h with conventional ceramic processing method. X-ray diffraction analysis indicated that the doped SnO 2 reacted with praseodymium oxides during sintering, generating Pr 2 Sn 2 O 7 phase. Through scanning electron microscopy, it was found that the doping of SnO 2 played a role against the growth of ZnO grains. Capacitance-voltage analysis revealed that the doped SnO 2 acted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…Figure 1 exhibits the differences of the apparent and relative densities of the varistor ceramics with various SnO 2 doping amounts. The apparent density of the varistors also raised obviously with the SnO 2 adding amounts up to 1.5 mol%, which may be attributed to the greater density of SnO 2 (6.995 g/cm 3 ) than that of ZnO (5.672 g/cm 3 ) as reported by Feng H., et al [7], and a few raise of relative density also observed (Figure 1). The huge ZnO discs densification at the high SnO 2 doping contents might be attributed to the SnO 2 doping impacts within the grain lattice, which led to the oxygen vacancies formation during the sintering step.…”
Section: Physical Analysissupporting
confidence: 70%
“…Figure 1 exhibits the differences of the apparent and relative densities of the varistor ceramics with various SnO 2 doping amounts. The apparent density of the varistors also raised obviously with the SnO 2 adding amounts up to 1.5 mol%, which may be attributed to the greater density of SnO 2 (6.995 g/cm 3 ) than that of ZnO (5.672 g/cm 3 ) as reported by Feng H., et al [7], and a few raise of relative density also observed (Figure 1). The huge ZnO discs densification at the high SnO 2 doping contents might be attributed to the SnO 2 doping impacts within the grain lattice, which led to the oxygen vacancies formation during the sintering step.…”
Section: Physical Analysissupporting
confidence: 70%
“…Varistors can detect and limit high transient voltage surges and can repeatedly endure such surges [1,2]. They are usually used to sense and limit transient voltage surges.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually used to sense and limit transient voltage surges. ZnO varistor ceramics show a highly nonlinear current-voltage characteristic with a highly resistive state in the pre-breakdown region that has a large non-linear coefficient [1][2][3][4][5][6][7][8][9][10]. Zinc oxide-based varistor ceramics are widely used in electronic appliances, such as voltage surge's protection devices, and especially in high-voltage lines.…”
Section: Introductionmentioning
confidence: 99%
“…For I vs V analysis, the Eq. 4 was used to check the nonlinear coefficient of curves [7,8]. α = (log E 2 -log E 1 ) -1 (4) where E 1 is the electrical field when current density is 1 mA/cm 2 and E 2 is the electrical field when current density is 10 mA/cm 2 .…”
Section: Methodsmentioning
confidence: 99%